The Impact Of Web Attributes On Millennial Travelling Decision - Hanim Tahir, Irbiana; Osman, Sharina (Opción, 2019)
Web technology has been Web technology has been developing over years to a point where companies can tailor the information they provide to custom- ers, adjusting the web page content according to the customer profile. Such adaptability can enhance sales by closely matching the customer needs and re- quirements. Particularly in travel industry, people can now scout for informa- tion related to specific destination through the social media platform including web page. This trend has becoming popular due to the several advantages that help shaped people’s intention to purchase travelling packages. In this study, the framework is developed based on Davis’ Technology Acceptance Model (TAM) correlate with the attributes of using website on a purchase intention process to travel. This conceptual paper discusses the previous lit- erature relating to the factors influencing the intention to purchase travelling packages among the millennial travellers in Kuala Lumpur. Hypotheses will be tested using relevant tests (colleration and relationship testing) and data will be collected using questionnaire among young traveller in Kuala Lumpur. A proposed theoritical framework that has been developed using Davis’ Tech- nology Acceptance Model (TAM) as underpinning theory. This paper is only focusing at the variables from the first Davis’ Technology Acceptance Model (TAM) that has been introduced by Davis, 1989. Contribution would be rele- vant in various school of thought of tourism as well as customer behavioural in purchasing and intention to buy product or services online.